2007
DOI: 10.1021/jf062838x
|View full text |Cite
|
Sign up to set email alerts
|

Strecker Degradation of Phenylalanine Initiated by 2,4-Decadienal or Methyl 13-Oxooctadeca-9,11-dienoate in Model Systems

Abstract: The reaction of 2,4-decadienal and methyl 13-oxooctadeca-9,11-dienoate with phenylalanine was studied to determine if alkadienals and ketodienes are able to produce the Strecker-type degradation of amino acids to the corresponding Strecker aldehydes. When reactions were carried out at 180 degrees C, both carbonyl compounds degraded phenylalanine to phenylacetaldehyde, among other compounds. The yield of the phenylacetaldehyde produced depended on the reaction pH and increased linearly with both the amount of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 21 publications
5
65
2
Order By: Relevance
“…Researches showed that some secondary lipid oxidation products can convert amino acids into the corresponding vinylogous derivatives Zamora et al 2007), and some lipid oxidation products can degrade asparagine to acrylamide ). They proposed α,β,γ,δ-diunsaturated carbonyl compounds as the most reactive, followed by hydroperoxides, likely because of their thermal decomposition upon heating.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Researches showed that some secondary lipid oxidation products can convert amino acids into the corresponding vinylogous derivatives Zamora et al 2007), and some lipid oxidation products can degrade asparagine to acrylamide ). They proposed α,β,γ,δ-diunsaturated carbonyl compounds as the most reactive, followed by hydroperoxides, likely because of their thermal decomposition upon heating.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…This is likely a consequence of the reactivity of these compounds, which can react with amino compounds in several other ways, in addition to contribute to its deamination. Thus, the formation of Strecker aldehydes and diverse heterocyclic compounds, among other reactions, has been described by carbonyl-amine reactions in amino acids/ alkadienals reactions mixtures [19][20][21]. All these results suggest the existence of diverse competitive pathways by which 3-aminopropionamide and 3-(alkylamino)propionamides are converted into acrylamide.…”
Section: Discussionmentioning
confidence: 91%
“…37,39 In fact, the ability of aldehydes and ketones for 35 degrading amino acids was similar in most experiments and differences found might be more related to differences in solubility among the different lipid oxidation products than differences in reactivity. 40 In addition, this reaction has also been described for lipid hydroperoxides, 41 although a free radical 40 mechanism is likely taking place in this degradation in addition to the contribution of the reactive carbonyls produced by Scheme 6 Strecker degradation of phenylalanine produced by glyoxal Scheme 7 Strecker degradation of phenylalanine produced by 4,5-epoxy-2-alkenals hydroperoxide decomposition.…”
Section: Other Degradative Pathways That Produce Strecker Aldehydes Amentioning
confidence: 87%
“…15 The Strecker degradation of amino acids produced by secondary lipid oxidation products was firstly described in 2004 for the formation of phenylacetaldehyde by phenylalanine degradation in the presence of epoxyalkenals, 26 and later extended to other lipid-derived reactive carbonyls. [36][37][38] aldehyde formation by lipid oxidation products is believed to be produced analogously to amino acid degradation by α-dicarbonyl compounds. Scheme 7 shows the reaction pathway for the degradation of phenylalanine in the presence of 4,5-epoxyalkenals.…”
Section: Other Degradative Pathways That Produce Strecker Aldehydes Amentioning
confidence: 99%